2008
DOI: 10.1007/s11104-008-9636-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the specificity of three root-feeders towards grasses in coastal dunes

Abstract: Among the root-feeding nematodes that accumulate in the rhizosphere of grasses in European dunes, the genus Pratylenchus is of special relevance given its diversity and distribution. Although different species of Pratylenchus have been reported in dune grasses, the specificity towards dune plants, a fundamental aspect of the biology of the species, has hitherto not been studied. Two inoculation experiments using different combinations of grasses and nematodes were performed. The multiplication and the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Experimentally, it has been shown that both species of Pratylenchus are able to cause damage at densities resembling those occurring in the field in dunes (Brinkman et al 2005;de la Peña et al 2008). The level of tolerance of A. arenaria is also different for each of the Pratylenchus species (de la Peña et al 2008). Both facts are in agreement with high reciprocal selection pressures between the plant and root-feeders.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Experimentally, it has been shown that both species of Pratylenchus are able to cause damage at densities resembling those occurring in the field in dunes (Brinkman et al 2005;de la Peña et al 2008). The level of tolerance of A. arenaria is also different for each of the Pratylenchus species (de la Peña et al 2008). Both facts are in agreement with high reciprocal selection pressures between the plant and root-feeders.…”
Section: Introductionmentioning
confidence: 86%
“…These migratory endoparasitic nematodes invade, multiply on, feed on and move through the root cortex of the host plant resulting in necrotic lesions that often promote secondary fungal infections (Back et al 2002). Experimentally, it has been shown that both species of Pratylenchus are able to cause damage at densities resembling those occurring in the field in dunes (Brinkman et al 2005;de la Peña et al 2008). The level of tolerance of A. arenaria is also different for each of the Pratylenchus species (de la Peña et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…are putatively being controlled is in agreement with the results of previous studies and suggests that these nematodes are regulated by horizontal control (Brinkman et al 2005a, b). The competition between these two genera of nematodes must be occurring through resource limitation, as both genera feed on the same plant (bottom-up control; De la Peña et al 2008). However, it seems that part of this competition effect is trait-mediated by P. penetrans, because it depends on its compatibility with the nematode host Meloidogyne spp.…”
Section: Indirect Effectsmentioning
confidence: 99%
“…Among the PPN found to be involved in marram grass decline, Meloidogyne maritima is considered to be the most aggressive, and is the only PPN found to reduce plant biomass in mesocosm field experiments (Brinkman et al 2005a), although other nematode species could reduce plant biomass in single-species inoculations in pot experiments (de la Peña et al 2008;Piskiewicz et al 2007). Plant-parasitic nematode diversity was found to have an idiosyncratic effect on plant biomass, with responses being dependent on nematode identity (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation